2019
DOI: 10.4014/jmb.1904.04041
|View full text |Cite
|
Sign up to set email alerts
|

Brewing Rutin-Enriched Lager Beer with Buckwheat Malt as Adjuncts

Abstract: Brewing with buckwheat as an ingredient has been proven to be successful in several previous studies. However, few studies have focused on the effects of buckwheat on the rutin content and antioxidant activity of beer. In order to develop a lager beer with high rutin content and desirable sensory characteristics, tartary buckwheat malt was used as a brewing adjunct. The results showed that the rutin-degrading enzyme was the key factor affecting the rutin content in the wort and beer. Compared to beer made usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…Rutin is a flavonoid found in buckwheat, a raw material widely used in the production of craft beers. In recent years, considering the importance of the physiological effects of rutin (anti-inflammatory activity, anti-arthritic, and antifungal effects in addition to helping to control some cancers, contributing to some neurological disorders, among others), buckwheat has been used as a substitute for other grains in the production of different types of beers [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rutin is a flavonoid found in buckwheat, a raw material widely used in the production of craft beers. In recent years, considering the importance of the physiological effects of rutin (anti-inflammatory activity, anti-arthritic, and antifungal effects in addition to helping to control some cancers, contributing to some neurological disorders, among others), buckwheat has been used as a substitute for other grains in the production of different types of beers [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Buckwheat is potentially suitable for use as a raw ingredient in beer brewing, especially for application in the production of gluten-free beers [4,55]. However, there are some technological issues to be taken into account when brewing buckwheat malt beers.…”
Section: Buckwheat (Fagopyrum Esculentum Moench)mentioning
confidence: 99%
“…The raw materials and the several procedures that take place during brewing (milling, mashing and fermentation) are responsible for beer being nutritionally rich in amino acids, carbohydrates, vitamins, minerals and phenolic substances [3]. The principal polyphenols that can be found in beer include phenolic acids, flavonoids, tannins, proanthocyanidins and amino phenolic compounds, and originate principally from malt and hops, contributing considerably to the colour, flavour and stability of beer [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results also suggested that gluten-free adjuncts (i.e., buckwheat) could improve the colloidal stability of the final beer when combined with specific process condition (i.e., alkalinized first steeping water in the malting process). Deng et al (2019) showed that tartary buckwheat malt can be used to replace (as adjunct) barley malt up to 20% or 40%, without affecting beer quality. The resultant buckwheat beers were found to be rich in rutin, a flavonoid, and exhibited good oxidative stability during forced aging.…”
Section: Pseudo-cereals (Quinoa Amaranth and Buckwheat)mentioning
confidence: 99%